THE RELATIONSHIP BETWEEN ORAL HEALTH MAINTENANCE KNOWLEDGE AND ORAL HYGIENE AMONG INMATES (WBP) IN CLASS IIA PRISON BANJARMASIN - Sabilal Arief; Galuh Dwinta Sari; Alexander Sitepu; R. Harry Dharmawan Setyawardhana; Diana Wibowo (FKG ULM, 2025)
Background: Knowledge is the basis for the formation of behavior. Limited access to information for inmates causes their knowledge of dental and oral health to decrease. The 2022 Annual Report of the Directorate General of Corrections recorded that 6,312 people were diagnosed with dental disease and were included in one of the five diseases that are often experienced by prisoners. Dental and oral diseases have a high ranking suffered by inmates, which is one of the indicators that the dental and oral hygiene of prisoners is not maintained. Objective: This study aims to know the relationship between oral health maintenance knowledge and oral hygiene in class IIA Banjarmasin prison inmates. Method: This study uses an observational analytical method with a cross sectional research design. The measurement of knowledge variables used a dental and oral health maintenance knowledge questionnaire, while the measurement of dental and oral hygiene used the Oral Hygiene Index Simplified (OHI-S). Result: The results of the somers'D test produced data with a significance value of 0.001 (ρ<0.05). The correlation coefficient value in the study was obtained at -0.463, indicating the relationship between the two moderate and negative variables, so that it has a reciprocal relationship. Conclusion: There is a relationship between oral health maintenance knowledge and oral hygiene among inmates (WBP) in class IIA Prison Banjarmasin Keyword: knowledge, oral hygiene, inmates.